Signalling pathways in endometrial cancer - Markowska, Anna; Pawałowska, Monika; Lubin, Jolanta; Markowska, Janina (Contemporary Oncology/Współczesna Onkologia, 2014)
Carcinogenesis is a multistage process, during which the activity of signalling pathways responsible for cell cycle regulation and division is disrupted which leads to inhibition of apoptosis and enhanced proliferation. Improper activation of Wnt/β-catenin and PI3K. Akt pathways play essential role in endometrial cancers (EC), mainly type I. Mutations in APC, axin or CTNBB1 may lead to β-catenin overactivation leading to excessive gene expression. PTEN inactivation, mutations in the PIK3CA or Akt result in increased transmission in the PI3K/Akt pathway, apoptosis inhibition, intensive cell division, mTOR excitation. In non-endometrioid cancers, key mutations include suppressor gene TP53 responsible for repairing damaged DNA or apoptosis initiation. Irregularities in gene P16, encoding a protein forming the p16-cyclinD/CDK-pRb have also been described. Understanding the complex relations between specific proteins taking part in signal transduction of the abovementioned pathways is key to research on drugs used in targeted therapy.